NYEs/SGRs‐mediated chlorophyll degradation is critical for detoxification during seed maturation in Arabidopsis. (20th October 2017) - Li, Zhongpeng; Wu, Shouxin; Chen, Junyi; Wang, Xiaoyan; Gao, Jiong; Ren, Guodong; Kuai, Benke
Summary: In the seed industry, chlorophyll (Chl) fluorescence is often used as a major non‐invasive reporter of seed maturation and quality. Breakdown of Chl is a proactive process during the late stage of seed maturation, as well as during leaf senescence and fruit ripening. However, the biological significance of this process is still unclear. NYE1 and NYE2 are Mg‐dechelatases, catalyzing the first rate‐limiting step of Chl a degradation. Loss‐of‐function of both NYE1 and NYE2 not only results in a nearly complete retention of Chl during leaf senescence, but also produces green seeds in Arabidopsis. In this study, we showed that Chl retention in the nye1 nye2 double‐mutant caused severe photo‐damage to maturing seeds. Upon prolonged light exposure, green seeds of nye1 nye2 gradually bleached out and eventually lost their germination capacity. This organ‐specific photosensitive phenotype is likely due to an over‐accumulation of free Chl, which possesses photosensitizing properties and causes a burst of reactive oxygen species upon light exposure. As expected, a similar, albeit much milder, photosensitive phenotype was observed in the seeds of d1 d2, a green‐seed mutant defective in NYE/SGR orthologous genes in soybean. Taken together, our data suggest that efficient NYEs‐mediated Chl degradation is critical for detoxification during seed maturation. Significance statement: Despite of the wide recognition that the residual Chl content is inversely associated with seed quality, the biological significance of rapid Chl degradation during seed maturation has been largely uninvestigated. In this study, we show that the Chl retention in seeds caused by defects of NYE s results in severe photo‐damage to maturing seeds and is consequently detrimental to seed germination.